Use of Oppositely-Polarized External Magnets to Improve the Accumulation and Penetration of Magnetic Nanocarriers into Solid Tumors - Liu, Jessica F. (ACS Nano, 2019)
Drug delivery to solid tumors is hindered by hydrostatic and physical barriers that limit the penetration of nanocarriers into tumor tissue. When exploiting the enhanced permeability and retention (EPR) effect for passive targeting of nanocarriers, the increased interstitial fluid pressure and dense extracellular matrix in tumors limits the distribution of the nanocarriers to perivascular regions. Previous strategies have shown that magnetophoresis enhances accumulation and penetration of nanoparticles into solid tumors. However, because magnetic fields fall off rapidly with distance from the magnet, these methods have been limited to use in superficial tumors. To overcome this problem, we have developed a system comprising two oppositely-polarized magnets that enables the penetration of magnetic nanocarriers into more deeply-seeded tumors. Using this method, we demonstrate a 5-fold increase in the penetration and a 3-fold increase in the accumulation of magnetic nanoparticles within solid tumors compared to EPR.